Isolated Mass-Forming IgG4-Related Cholangitis as an Initial Clinical Presentation of Systemic IgG4-Related Disease - Seokhwi Kim; Hyunsik Bae; Misun Choi; Binnari Kim; Jin Seok Heo; Ho Seong Kim; Seung Hee Choi; Kee-Taek Jang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
IgG4-related disease (IgG4-RD) may involve multiple organs. Although it usually presents as diffuse organ involvement, localized mass-forming lesions have been occasionally encountered in pancreas. However, the same pattern has been seldom reported in biliary tract. A 61-year-old male showed a hilar bile duct mass with multiple enlarged lymph nodes in imaging studies and he underwent trisectionectomy under impression of cholangiocarcinoma. Gross examination revealed a mass-like lesion around hilar bile duct. Histopathologically, dense lymphoplasmacytic infiltration and storiform fibrosis were identified without evidence of malignancy. Immunohistochemical stain demonstrated rich IgG4-positive plasma cell infiltration. Follow-up imaging studies disclosed multiple enlarged lymph nodes with involvement of pancreas and perisplenic soft tissue. The lesions have been significantly reduced after steroid treatment, which suggests multi-organ involvement of systemic IgG4-RD. Here, we report an unusual localized mass-forming IgG4-related cholangitis as an initial presentation of IgG4-RD, which was biliary manifestation of systemic IgG4-related autoimmune disease.